2017
DOI: 10.1186/s12864-017-3646-1
|View full text |Cite
|
Sign up to set email alerts
|

Population diversity of the genetically determined TTR expression in human tissues and its implications in TTR amyloidosis

Abstract: BackgroundTransthyretin (TTR) amyloidosis is a hereditary disease with a complex genotype-phenotype correlation. We conducted a literature survey to define the clinical landscape of TTR amyloidosis across populations worldwide. Then, we investigated whether the genetically determined TTR expression differs among human populations, contributing to the differences observed in patients. Polygenic scores for genetically determined TTR expression in 14 clinically relevant tissues were constructed using data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Furthermore, although those alleles are present in both AAs and EAs (MAF > 5%), we observed significant associations in the African-descent cohorts only. As also reported in other GWAS of substance use disorders [Smith et al, 2017], this may be due to the presence of epistatic interactions specific to African genomic background [Iorio et al, 2017; Karaca et al, 2016; Polimanti et al, 2015]. …”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, although those alleles are present in both AAs and EAs (MAF > 5%), we observed significant associations in the African-descent cohorts only. As also reported in other GWAS of substance use disorders [Smith et al, 2017], this may be due to the presence of epistatic interactions specific to African genomic background [Iorio et al, 2017; Karaca et al, 2016; Polimanti et al, 2015]. …”
Section: Discussionsupporting
confidence: 55%
“…In a recent study, we observed that genetically determined TTR expression varies across human populations and this variation appears to be in line with known epidemiological differences in the patients affected. 21 On this basis, we evaluated the impact of the non-coding variants on the genetically determined TTR expression in Italian patients with TTR amyloidosis. Indeed, we hypothesize that non-coding variation regulating TTR gene expression in source and target tissues is one of the mechanisms involved in the phenotypic heterogeneity observed among the patients affected by TTR amyloidosis.…”
Section: Introductionmentioning
confidence: 99%
“…These epidemiological findings indicate that atypical phenotypes occurring earlier in life could be connected to the risk of heart failure in Val122Ile carriers. Findings from several studies including ours raise the possibility of non-regulatory molecular factors contributing to the genotype-phenotype correlation 10,[14][15][16][17] . Therefore, understanding the underlying biological changes in Val122Ile carriers is key to explaining the symptom heterogeneity and earlier onset of atypical phenotypes.…”
Section: Introductionmentioning
confidence: 72%